2021
DOI: 10.1108/jtf-10-2020-0176
|View full text |Cite
|
Sign up to set email alerts
|

Reconnecting the space of tourism and citizenship: the case of tourists’ hubris

Abstract: Purpose The rapid growth of tourism prior to the COVID-19 pandemic prompts the need for critical reflection of tourism’s “local-global” responsibility in the wake of that pandemic. Conceptually driven by the ancient Greek notion of hubris, this study reflects on the perception of tourists as actors disconnected from citizens’ necessities, safety and well-being. In so doing we develop further knowledge on the relationship between the spaces of tourism and citizenship and how this might build a sustainable futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Apropos, national tourism destinations face a similar reorderingsome keeping their borders shut, subsidizing the domestic visitor economy, while others maintain open borders, risking an upsurge of COVID-19 cases to capture tourist expenditure (Tremblay-Huet and Lapointe, 2021). The pandemic crisis of 2020-2021 is reconnecting tourism to place-based roots, as Tomassini et al (2021) argue, leaving the paradigmatic tourist behind and reinscribing the tourist within citizenship and political responsibilityjoining the body touristic with the body politic.…”
Section: On Biopolitics and Tourism Crisis: Immunization Exception And Imaginariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Apropos, national tourism destinations face a similar reorderingsome keeping their borders shut, subsidizing the domestic visitor economy, while others maintain open borders, risking an upsurge of COVID-19 cases to capture tourist expenditure (Tremblay-Huet and Lapointe, 2021). The pandemic crisis of 2020-2021 is reconnecting tourism to place-based roots, as Tomassini et al (2021) argue, leaving the paradigmatic tourist behind and reinscribing the tourist within citizenship and political responsibilityjoining the body touristic with the body politic.…”
Section: On Biopolitics and Tourism Crisis: Immunization Exception And Imaginariesmentioning
confidence: 99%
“…Whose responsibility are systemic injustices (that are often hardly visible to tourists), such as socially and institutionally embedded racism against ethnic minorities and religious groups, oppression and exploitation of women and children, or historical injustices and dispossession from traditional lands due to imperialism or colonialism? "Justice Tourism" puts the onus on a few to act politically, but such efforts are often driven by humanitarian (moral) principles and disguise other issues and challenges (Guia, 2020;Tomassini et al, 2021).…”
Section: On Justice and Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Many publications have been produced the past three years about the impacts of COVID-19 on the tourism and hospitality sector and whether this is a game changer or not (Cheer et al, 2021;Lew (Information about the authors can be found at the end of this article.) Papp et al, 2023;Tomassini et al, 2021;Yeoman, 2023). Given that the COVID pandemic is quite a recent phenomenon affecting tourism, most of these papers remain conceptual show scenarios, visions and potential outlooks.…”
Section: Introductionmentioning
confidence: 99%
“…The sociological space of tourism, together with its practices, are largely the product of modern western culture and the production systems of neoliberal capitalism (Bianchi, 2018;Higgins-Desbiolles, 2018). In such neoliberal space tourism has been discussed as disregarding the needs and well-being of the local community (Higgins-Desbiolles, 2019a, 2019bTomassini et al, 2021) urging a call to action to socialise tourism . Conversely, we understand and investigate tourism as mobility praxis in an unjust spatiality and as a lack of affective relationships.…”
Section: Introductionmentioning
confidence: 99%